Opening our eyes to Global Health; a philosophy of universal values - Wass, Val (Perspect Med Educ, 2015)
Globalization is advancing at a pace. As we strive to introduce ‘Global Health’ into clinical curricula we risk fundamental misunderstandings unless we clearly define what we aim to achieve. Clinicians must be prepared for a life time of uncertainty, change and challenge. The fluctuating world arena will undoubtedly impact on their future work in ways we cannot predict. Population migration, climate change and shifts in cultural dominance are already at play. Global health risks being translated through the eyes of Western ideology as disease-based curricula focused paternalistically on ‘helping’ the developing world. We must not lack humility to open eyes to learning within the context of increasingly diverse environments and patient populations. Global health is as ‘local’ as it is ‘international’. It should be viewed, I argue, as a philosophy based on the values and expectations found within ourselves and our communities. Responding to globalization lies not only in knowledge but embraces human rights, justice and, most importantly, self-awareness. Knowledge is more easily translated into curriculum objectives. We risk letting future clinicians and their patients down if we ignore the other universal values.